2018
DOI: 10.1016/j.jaut.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Soluble antigen arrays disarm antigen-specific B cells to promote lasting immune tolerance in experimental autoimmune encephalomyelitis

Abstract: Autoreactive lymphocytes that escape central immune tolerance may be silenced via an endogenous peripheral tolerance mechanism known as anergy. Antigen-specific therapies capable of inducing anergy may restore patients with autoimmune diseases to a healthy phenotype while avoiding deleterious side effects associated with global immunosuppression. Inducing anergy in B cells may be a particularly potent intervention, as B cells can contribute to autoimmune diseases through multiple mechanisms and offer the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 57 publications
0
70
0
Order By: Relevance
“…6 SAgAs have been designed to bundle peptides / proteins together for more efficient uptake in vivo and, in some cases, achieve multivalent engagement of B cells. 7,8 In addition, SAgA uptake results in epitope presentation to targeted T cells in the absence of costimulation or proinflammatory cytokines, which may induce antigen-specific immune tolerance as a way to treat T1D. SAgAs are constructed using a hydrophilic linear polymer, hyaluronic acid (HA), grafted with multiple repeating epitopes from an autoantigen.…”
Section: Introductionmentioning
confidence: 99%
“…6 SAgAs have been designed to bundle peptides / proteins together for more efficient uptake in vivo and, in some cases, achieve multivalent engagement of B cells. 7,8 In addition, SAgA uptake results in epitope presentation to targeted T cells in the absence of costimulation or proinflammatory cytokines, which may induce antigen-specific immune tolerance as a way to treat T1D. SAgAs are constructed using a hydrophilic linear polymer, hyaluronic acid (HA), grafted with multiple repeating epitopes from an autoantigen.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow‐up study, Hartwell et al . elucidated the immunological mechanisms responsible for the development of tolerance to the PLP autoantigen.…”
Section: Multivalency In Immune Cell Modulationmentioning
confidence: 99%
“…[43,44] Building upon this work, Berkland and co-workers [45] next replaced the hydrolysable oxime bond (used to synthesize SA-gA PLP:LABL )w ith ah ydrolyticallys table covalent "Click" attachment (via Copper-catalyzed Azide-Alkyne Cycloaddition) to synthesize cSAgA PLP:LABL .T heir hypothesis was that this modification would help enhance and maintain the molecule'sa ction at the APC surfacet oi mprovee fficacy.T hey indeed saw that cSAgA PLP:LABL achieved efficacy equivalent to that of hydrolysable SAgA PLP:LABL at one-quarter of the dose when tested in a preclinical model for encephalomyelitis (EAE). [45] In af ollow-up study,H artwell et al [46] elucidatedt he immunological mechanisms responsible for the development of tolerancet ot he PLP autoantigen. They found that multivalent cSAgA PLP:LABL induced an anergic response in Bc ells and particularly as ubset of Bc ells-auto-immune associated Bc ells (ABCs)-that acted as potent APCs in auto-immune diseases.…”
Section: Multivalency In Immunosuppressionmentioning
confidence: 99%
“…Another approach harnessing multivalent delivery of self‐antigens to promote tolerance involves using low molecular weight polymers presenting self‐antigens to directly modulate interactions with B cells, termed “soluble antigen arrays.” B cells require antigen recognition of the B cell receptor to trigger B cell activation. However, repeated signaling through the B cell receptor (BCR) in the absence of a costimulatory signal can promote functional exhaustion or anergy.…”
Section: Nps and Mps Offer Attractive Features As Carriers Of Signalsmentioning
confidence: 99%